Food-based dietary guidelines - practical aspects of implementation - Walter, Paul; Elmadfa, Ibrahim (Karger, 2007)
This issue is a dedicated supplement published in addition to the regular issues of \'Annals of Nutrition and Metabolism\' focussing on one specific topic. \'Annals of Nutrition and Metabolism\' is a well-respected, international peer-reviewed journal in Nutrition. Supplement issues are included in the subscription.
Annals of nutrition & metabolism, ISSN 0250-6807 vol. 51, suppl. 2, 2007
Keywords: Diet Surveys; Feeding Behavior; nutriční hodnota; Nutritional Physiological Phenomena; celosvětové zdraví; výživová politika; Nutritional Requirements; nutriční nároky; Global Health; směrnice jako téma; Guidelines as Topic; stravovací zvyklosti; dieta - přehledy; Diet; Nutritional Sciences; Health Promotion; dieta; nutriční terapie, dietoterapie a výživa; fyziologie výživy; Nutritive Value; nutriční vědy; Nutrition Policy; podpora zdraví